Mutagenicity of heteroaromatic amines: Computational study on the influence of methyl substituents - Borosky, Gabriela Leonor (2016)
Quantum mechanical calculations were performed to elucidate the factors determining the variations in mutagenic activity within groups of isomeric heteroaromatic amines that differ in the position of methyl substituents. Formation energies for noncovalent complexes and covalent DNA adducts were evaluated by means of high level quantum chemical methods. According to the computational results in this work, covalent adduct stability is proposed to influence the relative mutagenicities of structurally related heterocyclic amines. The stability of covalent C8-dG DNA adducts was found to be mainly determined by π-stacking interactions between the fused ring system of the heteroaromatic amines and the flanking nucleobases. Relative mutagenicity of amines of very related structure is proposed to be regulated by both nitrenium ion and covalent adduct stabilities.